Survival benefits and safety of chemotherapy regimens for pancreatic cancer: An umbrella review of meta-analyses of randomized controlled trials - Aditi Kharat; Chia Jie Tan; Manit Saeteaw; Anindit Chhibber; Joseph Biskupiak; Sajesh K Veettil; Nathorn Chaiyakunapruk (Annals of Pancreatic Disorders and Treatment - Peertechz Publications, 2022)
Introduction: Several meta-analyses have reported the survival benefits and safety issues of chemotherapy regimens for pancreatic cancer (PC). The aim was to perform an umbrella review to summarize the existing evidence from meta-analyses of randomized controlled trials (RCTs).  Methods: EMBASE, PubMed, Cochrane database of systematic reviews, and Epistemonikos were searched from inception to October 31st, 2021.Methodological quality was assessed using the A Measurement Tool to Assess Systematic Reviews (AMSTAR-2). The quality of evidence was evaluated using GRADE criteria (Grading of Recommendations, Assessment, Development, and Evaluations). Results: A total of 2,732 records were identified with 24 articles corresponding to 168 meta-analyses in resected/metastatic PC. Two (8.3%) studies were found to be of high methodological quality. Eighty (47.6%) meta-analyses reported survival benefits of using combination chemotherapy, while 88 (52.4%) meta-analyses reported safety outcomes. 78 (46.42%; 36-efficacy, 42-safety outcomes) of the 168 meta-analyses were statistically significant (P ≤0.05). No meta-analyses were found to be of high-quality evidence. Twelve meta-analyses reporting the survival benefits of gemcitabine combinations were graded as moderate quality of evidence. Combination regimen FOLFIRINOX, gemcitabine nab-paclitaxel (gem/nab), and gemcitabine capecitabine (gem/cap) compared to gemcitabine monotherapy were found to improve overall survival (OS) and progression free survival (PFS) for both resected (OS: HR = 0.78 (0.69-0.89); PFS: HR=0.79 (0.66-0.94)) and advanced PC (OS: HR = 0.76 (0.68-0.85); PFS: HR = 0.68 (0.60 -0.78)). One meta-analysis comparing the gemcitabine combination regimens (with Nab/Paclitaxel or Capecitabine) versus monotherapy among metastatic PC patients was upgraded to high quality after a sensitivity analysis excluding small-sized studies (PFS; HR = 0.78 (95% CI, 0.69-0.88)). The remaining meta-analyses were either low or very low quality of evidence.  Conclusion: Our review showed that the use of combination chemotherapy regimens demonstrated survival benefits over gemcitabine monotherapy, which were supported by moderate to high-quality evidence. Gemcitabine combined with taxanes particularly showed high benefits for overall survival but only a modest benefit for progression free survival for metastatic PC. SWOG-1505 study compared perioperative FOLFIRINOX vs gem/nab in patients with resectable PC but no differences in survival was found. To date, FOLFIRINOX and gem/nab have been compared in the perioperative setting but no phase III trials have performed direct head-to-head comparisons for FOLFIRINOX against gemcitabine-based combination treatments in the metastatic setting. In future, head-to-head clinical trials comparing safety and efficacy for FOLFIRINOX vs gemcitabine-based combinations regimens (specifically gem/nab and gem/cap) in the metastatic setting are required.